Training on Using the Explicit Instruction Model to Support Students' Writing Skills at DDI Alliritengae, Maros Regency - Azis, Abdul; Ramly; Asia; Shafariana; Ilma Rahim; Rizki Herdiani (Institute of Education and Social Research, 2024)
The results of initial observations carried out in Class XII of Madrasah Aliyah DDI Alliritengae Maros, showed that the student was completely unable to write. Writing skills are still lacking because teachers find it difficult to teach writing skills. Likewise, learning techniques are still teacher-centred and students are less active in the learning process. Apart from that, teachers are less selective in choosing learning models, especially writing skills. Writing skills are one of students' language skills. At MA DDI Alliritengae Maros, Maros Regency, the use of the Explicit Instruction Model to support writing skills is increasingly being developed in the student environment. The Explicit Instruction model has been proven to have advantages in presenting the results of a writer's writing to other people. The results of data analysis provide a clear picture so that a correct understanding of the student's condition is related to the use of the Explicit Instruction Model in the writing process. High school students can optimize the performance of their writing skills through the Explicit Instruction Model to improve the quality of learning and make it easier to manage widely used writing.